Life Orientations of Migrant Students under Martial Law - Falko , Natalia; Serbin , Iyuriy; Hurtovenko , Nataliia; Tylnyi , Ivan (Insight: the psychological dimensions of society, 2024)
The aim is an empirical study of the life orientations of young people in conditions of sociogenic challenges. Methods. The study involved students who studied at three levels of educational programs: “Bachelor”, “Master”, “Doctor of Philosophy” at higher education institutions of Ukraine, with a total number of n = 112 people, aged 18 to 29 years (M = 23.43; SD = ±3.05). All respondents were internal or external migrants, which ensured the conditions of the sociogenic challenges they faced. Two groups of valid and reliable psychodiagnostic methods that reflect life orientations were used: the first – the “Life Orientation Test-Revised” (Carver & Gaines, 1987) and the “Value Orientations” by M. Rokeach (1973); the second concerned the behavior of the individual in the face of sociogenic challenges: the “Personal Readiness for Change Questionnaire” (Rollnick et al., 1992) and the “Way of Coping Questionnaire” (Lazarus & Folkman, 1984). Results. The ranking of the terminal and instrumental values of young people was carried out and it was determined that the terminal values (a proactive life attitude, health, and an interesting job) and instrumental values (self-control, education, and high requests) were prevalent. A correlation pleiad has been built and twenty-eight significant correlations of life orientations with the parameters of individual behavior in the face of sociogenic challenges and coping strategies have been clarified (p < .050; p < .010; p < .001). The existence of significant correlations with the parameters of personal readiness for change and constructive coping strategies has been clarified and explained. The most dependent values were a proactive life attitude and self-control. The latent danger was posed by negative expectations, the dominance of which can have fatal consequences for young people. Discussion and conclusions. It is substantiated that the study of life orientations of young people in the context of sociogenic challenges is examination of young people’ awareness and rethinking of their life purpose, the meaning of life, and the desire for self-realization. Life values, considered through the prism of dynamic social transformations, in the dimensions of readiness or unreadiness for personal changes and constructive and destructive coping strategies, confirmed the complexity and diversity of the phenomenon under study. It is noted that the obtained empirical results are of scientific value for all those who work with young people and seek constructive ways to overcome sociogenic challenges.
Keywords: value orientations; living space of young people; deviant behavior; stressors; social uncertainty; antisocial behavior; coping strategies; self-actualization